2020
DOI: 10.1371/journal.ppat.1008813
|View full text |Cite
|
Sign up to set email alerts
|

Variation in HIV-1 Nef function within and among viral subtypes reveals genetically separable antagonism of SERINC3 and SERINC5

Abstract: HIV Nef counteracts cellular host restriction factors SERINC3 and SERINC5, but our understanding of how naturally occurring global Nef sequence diversity impacts these activities is limited. Here, we quantify SERINC3 and SERINC5 internalization function for 339 Nef clones, representing the major pandemic HIV-1 group M subtypes A, B, C and D. We describe distinct subtype-associated hierarchies for Nef-mediated internalization of SER-INC5, for which subtype B clones display the highest activities on average, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 69 publications
(108 reference statements)
2
26
1
Order By: Relevance
“…Recent reports demonstrated that three specific sites in Nef, the amino acids 12 to 39, the ExxxLL motif (S163C) and the AP-2 binding site (R178G), were identified to be involved in Nef function [ 14 , 15 , 16 , 24 ] ( Figure 1 ). In addition, multiple amino acid variations in Nef (subtype B HIV-1) were identified to play a role in SERINC3 and SERINC5 antagonism [ 14 , 25 , 26 ] ( Figure 1 ) including 8R, 9S, 11P, 12G, 14A/P/S, 15A, 21K/R, 28E, 43I, N51T, 54D, 63E, 81F, H116N, 120F, V148L/X, 157N, 158K, 161N, M168I/X, 182E and 188S, of which some specifically affected SERINC3 (8R, 9S, 11P, 12G, 14A, 15A, 21K, 28E, 43I, 182E and 188S) or SERINC5 (14S, 21R, 54D, 63E, 81F, 120F, 157N and 158K) [ 26 ]. We analyzed primary Nef proteins obtained from 123 individuals with HIV-1 participating in the Amsterdam Cohort Studies for amino acid changes at the previously described positions and regions as compared to consensus B ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent reports demonstrated that three specific sites in Nef, the amino acids 12 to 39, the ExxxLL motif (S163C) and the AP-2 binding site (R178G), were identified to be involved in Nef function [ 14 , 15 , 16 , 24 ] ( Figure 1 ). In addition, multiple amino acid variations in Nef (subtype B HIV-1) were identified to play a role in SERINC3 and SERINC5 antagonism [ 14 , 25 , 26 ] ( Figure 1 ) including 8R, 9S, 11P, 12G, 14A/P/S, 15A, 21K/R, 28E, 43I, N51T, 54D, 63E, 81F, H116N, 120F, V148L/X, 157N, 158K, 161N, M168I/X, 182E and 188S, of which some specifically affected SERINC3 (8R, 9S, 11P, 12G, 14A, 15A, 21K, 28E, 43I, 182E and 188S) or SERINC5 (14S, 21R, 54D, 63E, 81F, 120F, 157N and 158K) [ 26 ]. We analyzed primary Nef proteins obtained from 123 individuals with HIV-1 participating in the Amsterdam Cohort Studies for amino acid changes at the previously described positions and regions as compared to consensus B ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We selected 20 primary Nef proteins from individuals with HIV-1 participating in the Amsterdam Cohort Studies that show amino acid variation in the AP-2 binding site, the ExxxLL motif, changes in the number of positively charged amino acids and length of the protein interaction site consisting of the amino acid residues 12–39 (AA 12–39) and contain the previously identified amino acid polymorphisms [ 14 , 25 , 26 ] ( Figure 3 ). The primary Nef proteins were cloned into expression plasmids and Nef expression by these constructs was demonstrated by Western blotting ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations